Edukasi Konsep 3R (Reduce, Reuse, Recycle) Melalui Metode Demonstrasi untuk Mengurangi Sampah Plastik Siswa Sekolah dasar 100 Desa Sulauwangi, Kecamatan Tanjung Kemuning, Kabupaten Kaur - Bdikar Anumtiko Ling Kricas; Sulistia Melanda; Deana Aurelia; Meylinda Holinda; Sendi Citra Liana (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The use of single-use plastic packaging in elementary school environments often leads to waste accumulation due to limited management facilities and low environmental literacy among students. This action research aims to analyze the implementation of waste management education based on the 3R concept (Reduce, Reuse, Recycle) through demonstration methods, as well as to measure the improvement of students' knowledge and skills in processing plastic waste. Using a mixed-methods approach, this study was conducted at SD 100 Sulauwangi Village, Tanjung Kemuning District, Kaur Regency, focusing on 4th and 5th-grade students as the main subjects. Data were collected using test techniques (pre-test and post-test questionnaires), structured observations, and documentation. The results indicated that the implementation of demonstration-based education and direct hands-on practice successfully bridged abstract environmental conservation concepts into concrete and interactive learning experiences. Cognitively, there was a significant increase in the students' average score from 42.50 (pre-test) to 86.25 (post-test), with an N-Gain Score of 0.76, categorized as highly effective. Psychomotorically and affectively, students demonstrated skills in turning used plastic bottles into functional crafts (such as verticulture pots and stationery holders) and adopted eco-friendly habits, including bringing reusable water bottles (tumblers) and sorting waste. This study concludes that 3R education using the demonstration method effectively integrates students' cognitive, affective, and psychomotor domains from an early age.